Interferenz bei Referenz im Übersetzungsprozess - Hansen, Gyde (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Reference with noun phrases can only be described by drawing on different branches of linguistics such as pragmatics, semantics, syntax, morphology, phonology and stylistics. In a contrastive analysis of the use of articles in pairs of languages such as Danish and German, it has been shown to be expedient to deal first of all with the material in terms of a common prag-matic and text-semantic tertium comparationis (i. e. comparative framework) and subsequently to include constraints from other levels of description. Although Danish and German are in fact closely related languages, they differ considerably with respect to reference and the use of articles, and these – at times quite complicated – differences lead to a great deal of interference in translation. In a series of experiments in which translation processes were studied using the computer program Translog (developed by Arnt Lykke Jakobsen of the Copenhagen Business School), it has been shown that an effective means of combatting reference-related interference relating to reference in translation processes is to give individual consultation, through which the information obtained from observations made during the transla-tion process and the individual strengths and weaknesses of translators can be combined with the insights of contrastive linguistics.